MODEL TPACK DAN VIDEO ANIMASI INTERAKTIF UNTUK MENINGKATKAN HASIL BELAJAR AKHLAK PADA SISWA SEKOLAH DASAR - Kosesa, Mala Deni; Herianingtyas, Nur Luthfi Rizqa; Dewi, Rosbanon (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
This study aims to improve student learning achievement in Islamic Religious Education, specifically the moral lesson